There's a frog in my throat : 440 animal sayings a little bird told me - Leedy, Loreen (New York : Holiday House, 2003)
A collection of over 400 familiar and not-so-familiar sayings that have to do with animals, with each expression explained.
Includes index.
Maine Student Book Award list 2004-2005
Keywords: English language -- Terms and phrases -- Juvenile literature; Animals -- Nomenclature (Popular) -- Juvenile literature; Animals -- Folklore -- Juvenile literature; Figures of speech -- Juvenile literature; English language -- Terms and phrases; Figures of speech; Animals -- Folklore